An Insight into Different Stabilization Mechanisms of Phenytoin Derivatives Supersaturation by HPMC and PVP. Issue 8 (8th June 2015) - Otsuka, Naoya; Ueda, Keisuke; Ohyagi, Naoko; Shimizu, Kozue; Katakawa, Kazuaki; Kumamoto, Takuya; Higashi, Kenjirou; Yamamoto, Keiji; Moribe, Kunikazu
<x xml:space="preserve">Abstract</x> In this study, we examined the stabilization mechanism of drug supersaturation by hypromellose (HPMC) and polyvinylpirrolidone (PVP). The poorly water‐soluble drugs, phenytoin (diphenylhydantoin, DPH), and its synthesized derivatives monomethylphenytoin (MDPH) and dimethylphenytoin (DMDPH) were used. DPH supersaturation was efficiently maintained by both HPMC and PVP. HPMC maintained the supersaturation of MDPH and DMDPH in a similar manner to that of DPH, whereas the ability of PVP to maintain drug supersaturation increased as follows: DPH > MDPH > DMDPH. Caco‐2 permeation studies and nuclear magnetic resonance measurements revealed that the permeability and molecular state of the drug in a HPMC solution barely changed. In fact, the solubilization of the drug into PVP changed its apparent permeability and molecular state. The drug solubilization efficiency by PVP was higher and followed the order: DPH > MDPH > DMDPH. The different drug solubilization efficiencies most likely result from the different strengths in the intermolecular interaction between the DPH derivatives and PVP. The difference in the stabilization mechanism of drug supersaturation by HPMC and PVP could determine whether the efficient maintenance of the drug supersaturation was dependent on the drug species. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2574–2582, 2015